Strategic Business Plan Development for A Sawn Timber Trading Company: An Internal-External Analysis and Investment Feasibility Approach - Kurnianto, Anton; Handrito, Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to formulate an appropriate business plan for PD Terus Jaya to strengthen its competitiveness and support business expansion as a supplier of sawn timber products in response to increasing market opportunities. Design/Methodology/Approach – This study employs a qualitative descriptive approach. Data were collected through interviews, observations, and document studies. The company’s internal and external conditions were analyzed, and the Business Model Canvas (BMC) was applied as a foundation for developing strategies related to product/service, marketing, operations, organization, and financial planning. Findings – The results indicate that PD Terus Jaya is feasible for business development based on five analyzed investment feasibility criteria. The formulated business plan is recommended for immediate implementation to strengthen the company’s position as a sawn timber supplier and to take advantage of growing market demand. Originality/Value This research provides value by applying the Business Model Canvas to formulate an integrated business plan for a sawn timber trading company, offering strategic guidance that supports feasible investment decisions and sustainable business expansion.